Dampak Penggunaan E-Puskesmas dalam Meningkatkan Efektivitas Pelayanan Kesehatan di Puskesmas Pancur Kota Tanjungpinang - Dwi Wahyuni Putri; Dian Prima Safitri; Firman Firman (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
E-Puskesmas is a solution to problems caused by manual systems. It was created to streamline the method of reporting data to the Health Office and digitize the process of providing health services to the community at the Puskesmas. In addition, the online reporting system facilitates the dissemination of information effectively and efficiently. This study aims to determine the impact of using E-Puskesmas in improving the effectiveness of health services at the Pancur Community Health Center in Tanjungpinang City. The research method used is descriptive research with a qualitative approach conducted through observation, interviews, and documentation. The results of the study indicate that the implementation of E-Puskesmas has brought significant improvements in managing patient data, appointment scheduling, and reporting processes to the Health Office. Health workers find the system beneficial for storing accurate data, reducing paperwork, and enabling faster coordination with other health facilities. However, the use of the system is still hampered by unstable or slow internet or Wi-Fi networks, which often delay data input and retrieval during busy operational hours. This issue not only reduces efficiency but also causes frustration among staff who rely on the system for daily activities. The conclusion of this study highlights that the use of E-Puskesmas is effective in supporting digital health services but remains suboptimal due to technical challenges. Improving internet connectivity is critical to ensuring seamless operation and maximizing the benefits of the system. The study recommends that the local government and relevant stakeholders enhance the quality of network infrastructure and provide regular technical support and training for Puskesmas staff. By addressing these challenges, the Pancur Community Health Center can improve the stability of its operations and ensure that the E-Puskesmas application delivers optimal results in supporting high-quality, efficient, and technology-driven health services for the community.